2022
DOI: 10.1186/s13046-022-02316-2
|View full text |Cite
|
Sign up to set email alerts
|

OVOL2 impairs RHO GTPase signaling to restrain mitosis and aggressiveness of Anaplastic Thyroid Cancer

Abstract: Background Anaplastic Thyroid Cancer (ATC) is an undifferentiated and aggressive tumor that often originates from well-Differentiated Thyroid Carcinoma (DTC) through a trans-differentiation process. Epithelial-to-Mesenchymal Transition (EMT) is recognized as one of the major players of this process. OVOL2 is a transcription factor (TF) that promotes epithelial differentiation and restrains EMT during embryonic development. OVOL2 loss in some types of cancers is linked to aggressiveness and poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 94 publications
(82 reference statements)
1
2
0
Order By: Relevance
“… 27 Multiple studies have shown that OVOL2, as a transcription factor, inhibits EMT in tumor cells. 22 , 28 , 29 This result is consistent with our research results. In the current work, the downregulation of OVOL2 promoted cell proliferation, migration, invasion, and EMT.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… 27 Multiple studies have shown that OVOL2, as a transcription factor, inhibits EMT in tumor cells. 22 , 28 , 29 This result is consistent with our research results. In the current work, the downregulation of OVOL2 promoted cell proliferation, migration, invasion, and EMT.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have confirmed that OVOL2 plays an important role in tumor development and metastasis. 20 , 21 , 22 In our study, we first found that the expression level of OVOL2 was significantly reduced in LUAD tumor tissues and negatively correlated with the OS and DFS of patients with LUAD using a large-scale LUAD tissue microarray. Low OVOL2 expression was an independent risk factor in patients with LUAD that had poor prognosis and was significantly associated with clinicopathological features, such as tumor size, LN metastasis, and TNM stage.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, these genes display enrichment in their regulatory regions for a motif recognized by the transcription factor OVOL2 (Supplementary S1) that is known to be involved in angiogenesis and heart formation [39]. Although there is no data supporting its association with cardiac pathologies, OVOL2 has recently been associated with corneal dystrophy and various types of tumors, such as lung cancer and thyroid cancer [40][41][42]. To the best of our knowledge, its role in cardiac disorders has not been previously reported [39].…”
Section: Transcriptome Changes In Patients With Cardiac Pathologiesmentioning
confidence: 99%